EXAMINATION OF THE FINANCIAL STATEMENTS AS A TOOL FOR MINIMISING THE RISK OF BUSINESS UNITS - Węgrzyńska, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
Examination of financial statements is to provide meaningful information on the accuracy, the reliability of financial data and information in financial statement. Financial revisions shall be carried out under the national accounting law. During the test, the individual reports of the financial statements the statutory auditor is obliged to determine the risks for the audited entity. The purpose of this article is an attempt to present the creatures, the importance of auditing in minimizing business risk.